Development of convergent adaptations reveal highly conserved early ontogenetic skull shape in fishes with amphibious vision - Philipp Thieme; Vivian Fischbach; Ioannis Papadakis; Timo Moritz (Scientific Reports)
Abstract The development of skeletal elements in fish is strongly influenced by the functional demands and environmental constraints they face during different life stages but mostly occurs during their larval development. One example of late modifications within the skeletal system is the adaptation of the skull and eye morphology that allows for amphibious vision in the four-eyed fishes Anableps spp. Another species that is equally capable of simultaneous aquatic and aerial vision, Rhinomugil corsula, has been widely neglected in this field of research, although it presents great opportunities for comparative analyses on the evolution of this ability. We studied the development of the skull and eyes of Rhinomugil based on morphological, morphometric, and histological data. While cross sections reveal that the eyes develop required morphological adaptations for simultaneous amphibious vision in larval life stages, the restructuring of the neurocranium which causes the dorsolateral relocation of the eyes occurs only during late juvenile development. In Rhinomugil and Anableps, restructuring of the skull and eye occurs during similar developmental phases suggesting that the development of the skull shape is widely conserved and cannot easily be changed during larval development.